SAT0041 GENOTYPE OF THE RHEUMATOID ARTHRITISSEVERITY LOCUS, RS26232, IS ASSOCIATED WITH INVASIVENESS OF RASFS IN VITRO. (June 2019) - Dorris, Emma; Flanagan, Eimear; Linnehan, Eimear; Trenkmann, Michelle; Creevey, Karen; Veale, Douglas; Fearon, Ursula; Wilson, Gerry
Abstract : Background: The single nucleotide variant rs26232 has been associated with both the susceptibility to, and severity of, rheumatoid arthritis (RA). There is an allele dose response between rs26232 and radiological damage, with the minor, T, allele being protective against disease severity. Rs26232 is situated in the first intron of C5orf30, which is a negative regulator of tissue damage and inflammation in RA. Objectives: The objective of this study is to elucidate the mechanism by which rs26232 may mediate disease severity. We also aimed to determine the genotype-phenotype association of rs26232 in rheumatoid arthritis synovial fibroblasts (RASF). Methods: RASF were derived from knee biopsies of RA patients taken at arthroscopy (n=33). RASFs were used between passages 3-8. Matrigel-coated Boyden transwell chambers were used to measure invasion. Wound healing (scratch assays) were used to measure migration, whereas proliferation was measured via crystal violet staining of fixed RASF. Intracellular cytokine staining and cell surface markers were measured via flow cytometry. Secreted cytokines were measured in the supernatant of RASF using ELISA. Rs26232 genotype was determined by PCR genotyping assay with allelic discrimination analysis. Anticitrullinated protein antibody (ACPA) status was measured for each participant. Quantitative real-time PCR was used to measure gene expression. Mann-Whitney U test was used to compare two independent groups, Kruskal-Wallis test was used to compare groups of greater than two. Results: 49% (n=16) of our RASF cohort where homozygous for the major allele CC, 42% (n=14) were heterozygous CT, 9% (n=3) were TT. Rs26232 is associated with invasion of RASFs with the CC genotype being more invasive than the CT genotype (p=0.021). RASFs with the CC genotype had increased ICAM1 and VEGF cell surface expression compared to CT genotype (p=0.001, p=0.05 respectively). MCP1/CCL2 was decreased in CC compared to CT (p=0.013). No association was found between rs26232 genotype and migration, proliferation, or expression of MMP3, TIMP3, IP10 or MIP1a. rs26232 is located in the first intron of C5orf30. There was no differential expression of total C5orf30 or with any of the 3 individual transcript variants in rs26232 genotype groups. In silico analysis of the region in which rs26232 is located on chromosome 5 identified a DNase Hypersensitivity cluster. Furthermore, mining of the Genotype-Tissue Expression (GTEX) expression quantitative trait loci (eQTL) database revealed a cluster of genes located upstream on chromosome 5 (102, 850, 000-103, 150, 000) associated with rs26232. This region upstream from rs26232 contains 4 genes (EIF3KF1, PPIP5K2, PAM and GIN1), of which three are eQTLs of rs26232. In silico analysis revealed that the 3 eQTLs (EIF3KF1, PPiP5K2 and PAM) also contain the active enhancer mark H3K27Ac, whereas GIN1 does not. Conclusion: The CC genotype of rs26232 is associated with both increased invasiveness of RASFs and increased adhesion markers compared to CT genotype. Rs26232 does not mediate its affect via its nearest gene, C5orf30 . Rather, in silico analysis predicts rs26232 may function as a distal regulator of EIF3KF1, PPIP5K2 and PAM . Future work will test the hypothesis that rs26232 genotype phenotype association is mediated by EIF3KF1, PPIP5K2 and PAM. Disclosure of Interests: None declared